All-optical signal amplifier and distributor using cavity–atom coupling systems. (14th March 2016) - Duan, Yafan; Lin, Gongwei; Niu, Yueping; Gong, Shangqing
Abstract: We report an all-optical signal amplifier and a signal distributor using cavity–atom coupling systems. In this system we couple atoms with an optical cavity and realize the great enhancement of a control laser by the cavity with the help of two high coupling lasers. By this effect, we can use one weak control field to control another strong target field and the intensity changes are linear with our experimental conditions. This can be used as an all-optical signal amplifier, also known as a 'transphasor'. In our experiment, the gain of the weak field to strong field can be as high as 60. Furthermore, we can realize the distribution of optical signals, if we coordinate multiple cavity–atom coupling systems.